Development of Holonic Workforce Allocation in Electronics Assembly. - Lee, Zi Wei (2017)
Workforce allocation is a vital chain in the shop floor management especially for job shop model because it is the key factor that will directly influence the end-to-end productivity of the production line. This research is based on a case study in a global electronics manufacturing company located in Batu Gajah, Perak. Company X specializes in manufacturing electronics components such as power inductor and electromagnetic interference (EMI) suppression filter. Electrical sorting and taping (EST) process which is one of the manufacturing processes of power inductor is focused in this study as it involves the most number of operators and machines where proactive improvement is needed to maximize the output of the manufacturing system. The work tasks and machine allocation in the current manufacturing process of EST were studied and analyzed to determine the limitations of the current EST manufacturing system. Machine interference problem is one of the common issues faced by the EST process that causes the reduction in machine efficiency due to restricted workforce flexibility. In the EST manufacturing line studied, machine interference is identified in two aspects, primarily shortstop interference and setup interference. Holonic Manufacturing System (HMS) was proposed in this study to improve the flexibility in workforce planning. By using the concept of HMS, four possible cases with distinct work tasks allocation between the operators and the water spider are proposed. The future model was constructed based on the best case that could result in highest machine efficiency and most effective in resolving machine interference problem. The average machine efficiency of the EST process and the ability of EST process to deal with production issues such as multiple machine breakdowns and absence of worker could be improved with the implementation of holonic workforce allocation.